Investigation of wear behaviour and surface analysis of a coated H13 material for friction drilling application - Saravanan Balakrishnan; Selvakumar Subbaiah; Mathew Alphonse; Robert Cep; Sachin Salunkhe; Emad Abouel Nasr (PLoS ONE, 2025)
In recent years, industries have seen many advancements in finding proper tools for machining to enhance productivity. Choosing a proper friction drilling tool that minimizes surface damage and improves tool life and productivity is essential. In this study, the wear characteristics of H13 steel among four samples (untreated, heated, TiAlN, and AlCrN) were investigated through a pin-on-disc machine, focusing on highlighting the wear behaviour and surface morphology. The novelty of this study is to analyze an optimal friction drilling tool that can enhance its life. The tempering process was carried out to improve the hardness of the H13 steel tool from 37 HRC to 57 HRC. During the wear test process, the temperature is maintained at 250°C. Using an Atomic Force Microscope (AFM), the worn surface of the samples was analyzed. Among the four samples (untreated, heated, TiAlN, and AlCrN), the untreated samples were affected by adhesive wear and oxidation. It is observed that the tempering helps the coated H13 samples to appear wear-resistant; the material loss obtained for the coated samples is much less compared to the uncoated samples. The untreated and heated sample CoF values observed are 0.713 and 0.591; for TiAlN and AlCrN, the CoF values observed are 0.481 and 0.416. This study reveals that AlCrN Coated H13 steel exhibited the best wear response. Hence, it is suitable for Friction drilling applications.